Egg Development and Larvae and Juveniles Morphology of Carp, Cyprinus carpio in Korean - Park, Jae Min (Dev Reprod, 2017)
This study was conducted to observe egg and larvae morphological development of carp to obtain basic data for resource conservation and taxonomic research. Brood carp used in the research (total length 67.3-75.5 cm, average 71.0±3.45 cm) were bred in a circular rearing aquarium (600×300×100 cm) using a running water system from January to July, 2015. Breeding water temperature was maintained at 23.0-25.0℃(average 24.0℃). Fertilized carp eggs were translucent and globular, and their size was 1.75-1.89 mm (average 1.82±0.06 mm). Blastoderms formed 10 min after fertilization and reached the two-cell stage 30 min after fertilization. Then, the embryo turned dark and exhibited melanophores, and blood started flowing from the heart across the egg yolk at 42 hrs and 50 min after fertilization. Hatching began 70 hrs and 26 min after fertilization larvae emerged through the egg membrane, starting from the head. The length of prelarvae immediately after hatching was 5.23-5.38 mm (average 5.31±0.11 mm) the mouth and anus were closed, and the pectoral fin was formed. Postlarvae at 18 days after hatching had a total length of 11.9-13.9 mm (average 12.9±1.40 mm), separate anal fin and back membranes, and fin ray. Juveniles fish at 35 days after hatching had a total length of 29.9-30.2 mm (average 30.1±0.13 mm), with the body covered with scales, and the same number of fin rays, color, and shape as their broodstork.